Development of Supervision Systems Integrated to Increase the Efficiency of Embarkation and Debarkation of Passenger Ships: Case Study KM. Gunung Dempo - Rizky, Syabania Baitul; Kristiawan, Dedy; Kuncowati, Kuncowati (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2025)
Embarkation Debarkation is the process of boarding and disembarking ship passengers. Disruptions to the embarkation and disembarkation process can cause the ship to be late or not according to the ship's schedule. This research aims to investigate disruptions in the embarkation and disembarkation process on passenger ships KM. Gunung Dempo. Through case studies and analysis, researchers evaluate the impact that ship delays have on passengers, especially passenger ships KM. Gunung Dempo. Researchers also carried out an analysis of the causes of ship delays. The research results showed that ship delays were caused by the embarkation and disembarkation processes not being smooth, there were many disruptions to the embarkation and disembarkation processes such as hawkers and ship workers who boarded and disembarked irregularly in large numbers. It was found that the biggest cause of ships experiencing delays was the embarkation and disembarkation process. This finding highlights the importance of maintaining regulatory compliance, order and ship security.